FACTOR ANALYTIC INSIGHTS INTO MICRO-TEACHING PERFORMANCE OF TEACHER CANDIDATES - Atakan Ata; Kadir Kozan (Informascope, 2018)
This study investigated the factor structure of the intern keys teacher candidate assessment instrument used to assess micro-teaching performance of teacher candidates. In other words, the purpose of the current study was to explore the construct validity of the assessment tool which is considered to consist of one overarching construct: teaching effectiveness. To this end, an exploratory factor analysis in addition to a parallel analysis were employed using the ratings of 116 faculty members at various U.S. universities who supervised the teacher candidates' performance in their final semester. The results indicated a one-factor structure and high reliability indices. All these findings align with theoretical assumptions and call for further factor analytic studies on the instrument using different samples.